Complexity of Unsolved Forest Tenurial Conflict: A Case of Way Terusan Forest Management Unit, Lampung Province, Indonesia - Christine Wulandari; Yulia Rahma Fitriana; Indra Gumay Febryano; Susni Herwanti; Hari Kaskoyo; Hendika Jaya Putra (Jurnal Manajemen Hutan Tropika, 2021)
Effective forest management is challenging to achieve when there is uncertainty about who controls forest areas. Land tenure issues can arise from local communities, immigrants, the private sector, or the government. Overlapping rights in forest areas are very likely to occur due to the licensing system's lack of integration and the inaccuracy with which the problem of forest land use claims. The Forest area of Register 47 is the case where the forest tenurial conflict resolution is theoretical and takes into account the existence of forest communities and conflict resolution programs that have been implemented by the Forest Management Unit (FMU). This study employed case study approach carried out with an in-depth study in the historical study about the conflicts and juridical review in Way Terusan FMU, Lampung Province. The collected data was then validated by triangulating scheme by the observation and documentation. The findings show that in terms of legal, FMU is the legal authority in forest area organizations, especially after regional regulation since 2019. However, the encroachment began in the 1990s when about 900 households were relocated to the area without the Forestry Ministry accord. Various legalization permits were submitted to the central government, but they were not deemed as a viable option. Since the regional regulation of forest area law's introduction in 2019, the FMU has been the primary actor in forest management. In order to resolve all conflicts, the FMU might apply for some effective forestry partnership cooperation programs.